It's Good to Talk: Discussion in Blended Learnng Courses in the Context of Continued Professional Development for Solicitors - Rory O'Boyle (Irish Journal of Academic Practice, 2012)
This paper evaluates (a) student perceptions of blended learning in the context of continued professional development courses for solicitors and (b) student experience of discussion in such a blended learning course. Students in the Law Society of Ireland‟s Diploma in Employment Law partook in a blended learning course that contained face-to-face discussion and both asynchronous and synchronous online discussion as an essential feature of their learning experience. Students were asked to respond to self-completion interim and final questionnaires. The results suggest that „time poor‟ solicitors strongly approve of blended learning and their characteristics as independent, self-motivated learners mean they are well placed to fully participate in this form of learning; each method of discussion is valued by such students; the forms of such discussion, whether face-to-face, asynchronous or synchronous online discussion, can be complementary; the method of assessment has an important impact on student perceptions of the value of online discussion; and particular attention must be paid to framing synchronous discussion for it to be effective. With respect to implications for practice, the study confirms that blended learning is a valid means of course delivery in respect of continued professional development courses for solicitors and that such "time-poor" learners respond well to structured online discussion requiring mandatory postings. Key